Targeting alternative splicing as a novel approach to chemotherapy induced peripheral neuropathy - Swift, Matthew N. (2021)
Chemotherapy induced peripheral neuropathy (CIPN) is one of the most prevalent adverse effects of many chemotherapy drugs. It is estimated that up to 85% of patients suffer from CIPN during treatment and in many patients, painful neuropathy can continue beyond cessation of chemotherapy. Common symptoms of CIPN include, thermal and mechanical allodynia and painful sensations that are commonly described as burning and shooting pain. CIPN is often a dose limiting factor in the provision of chemotherapy. Currently, there are no effective treatments capable of preventing or treating CIPN. Consequently, CIPN is becoming an increasingly significant healthcare burden.